2015
DOI: 10.1051/0004-6361/201526195
|View full text |Cite
|
Sign up to set email alerts
|

Decayless low-amplitude kink oscillations: a common phenomenon in the solar corona?

Abstract: Context. We investigate the decayless regime of coronal kink oscillations recently discovered in the Solar Dynamics Observatory (SDO)/AIA data. In contrast to decaying kink oscillations that are excited by impulsive dynamical processes, this type of transverse oscillations is not connected to any external impulsive impact, such as a flare or coronal mass ejection, and does not show any significant decay. Moreover the amplitude of these decayless oscillations is typically lower than that of decaying oscillation… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

42
237
7

Year Published

2016
2016
2019
2019

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 191 publications
(286 citation statements)
references
References 36 publications
42
237
7
Order By: Relevance
“…Small-amplitude undamped kink oscillations are observed continuously without any visible driver. Similar to the oscillations in the decaying regime, the period of undamped kink oscillations was found to scale with the loop length (Anfinogentov et al 2015). Assuming that the small-amplitude undamped kink oscillations are subject to the same damping mechanism as the large-amplitude, rapidly decaying kink oscillations, there should be some mechanism that continuously supplies the oscillating loops with energy to compensate the damping.…”
Section: Introductionmentioning
confidence: 76%
See 3 more Smart Citations
“…Small-amplitude undamped kink oscillations are observed continuously without any visible driver. Similar to the oscillations in the decaying regime, the period of undamped kink oscillations was found to scale with the loop length (Anfinogentov et al 2015). Assuming that the small-amplitude undamped kink oscillations are subject to the same damping mechanism as the large-amplitude, rapidly decaying kink oscillations, there should be some mechanism that continuously supplies the oscillating loops with energy to compensate the damping.…”
Section: Introductionmentioning
confidence: 76%
“…Wang et al 2012;Nisticò et al 2013). Using the observations of undamped oscillations in 21 non-flaring active regions (NOAA 11637-11657) observed in January 2013 in the 171 Å channel of SDO/AIA (Anfinogentov et al 2015), we constructed scalings of the oscillation amplitudes with the period and loop length (Fig. 2).…”
Section: Observational Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Goddard et al (2016) studied the distributions of the oscillation parameters, such as the derived kink speed, as well as the damping of the oscillations. In contrast to this strongly damped regime, low amplitude decay-less kink oscillations have also been detected Anfinogentov et al 2013) and confirmed to be a common phenomenon in the corona (Anfinogentov et al 2015).…”
Section: Introductionmentioning
confidence: 79%